Nanofillers for Sustainable Applications - Nurazzi, N. M.; Bayraktar, E.; Norrrahim, M. N. F.; Aisyah, H. A.; Abdullah, N.; Asyraf, M. R. M. (Emerging materials and technologies, 2024)
"Nanofillers for Sustainable Applications provides an in-depth review of the wide-ranging applications of nanofillers. It explores both synthetic and natural nanofillers and focuses on their use as reinforcement and active fillers in composite structures. Covering various aspects of nanofillers, including synthesis methods, characteristics, properties, and compatibility, the book highlights the potential of nanofillers as functional materials for different applications and offers a collection of comparative studies to showcase their efficacy. It emphasizes sustainability, intelligent design, and high-end applications in fields such as packaging, pulp and paper, aerospace, automotive, medicine, chemical industry, biodiesel, and chemical sensors. The book is organized into several sections, covering topics such as synthetic nanomaterials, nanosafety, natural nanofillers, polymer composites, metal nanofillers, nanofillers in various industries, nanofillers in renewable energy, nanofillers in biomedical sectors, and nanofillers in automotive and aerospace industries. The book will be a useful reference for undergraduate and graduate students and academic researchers in the fields of materials science, nanomaterials, and polymer composites"--